Bounded rationality in differential games - Klaus B. Beckmann; Ralf Dewenter (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2017)
The present paper proposes a myopic, boundedly rational heuristic for individual decision-making in differential game settings. I demonstrate that this type of behaviour converges to Nash equilibrium in infinitely repeated stage games without a state variable if the stage game is strategically symmetric. Two examples are used to illustrate the application of the heuristic in differential games.
Keywords: C72; 330; differential games; simulation; bounded rationality